Pelaksanaan Pembagian Warisan Terhadap Ahli Waris Berdasarkan Kompilasi Hukum Islam di Desa Kualu Kecamatan Tambang - Muhammad Abdi; Muhammad Azani (Jurnal Hukum Respublica, 2020)
Problems in the implementation of inheritance are still common in the community today. This is due to the lack of public understanding of the procedures for the implementation of inheritance and the lack of public awareness to learn the provisions in the Compilation of Islamic Law regarding the procedures for the distribution of inheritance and the lack of socialization carried out by the Village Government and the Office of Religious Affairs towards the community regarding how to carry out the distribution of inheritance. One problem that occurs in the implementation of the distribution of inheritance is regarding an uncle who also gets a share of the inheritance even though all the main heirs of the testator are still complete and the last child gets more share of the inheritance even though the last child is a girl who has a daughter other siblings, the size of each heir is determined by an uncle. The research method used in this study is the law of sociological research. The data collection technique used is the method of observation, interview, questionnaire, and literature review. The results of this study are that the implementation of inheritance distribution implemented by Kualu Village community is still wrong and not in accordance with the provisions contained in the Compilation of Islamic Law. The inhibiting factor is the lack of knowledge and public insights on how to carry out the correct distribution of inheritance according to the compilation of Islamic law. Efforts should be made to hold socialization to the public about how the implementation of the distribution of inheritance is good and right according to the compilation of Islamic law, and increase public awareness to learn more about how to carry out the distribution of inheritance according to Islamic law compilation.